Value Distribution of Differential Polynomials which Involve Two Distinct Transcendental Meromorphic Functions - Banerjee, Dibyendu; Pal, Papai (Journal of Nepal Mathematical Society, 2025)
In the present note we deal with the value distribution of differential polynomials which involve two distinct transcendental meromorphic functions and obtain analogous results of Bhoosnurmath, et.al. for such kind of differential polynomials.